Gastronomic tourism: A case study of ecofeminism in local food promotion - S.E Mandaru, Silvania; Leuape, Emanuel Sowe; Meilawati, Fitria Titi (Bricolage : Jurnal Magister Ilmu Komunikasi, 2025)
Gastronomic tourism is a growing sector that intertwines cultural heritage, local food promotion, and sustainable practices. In this context, ecofeminism explores the intersection of environmental sustainability and gender roles, emphasizing women's contributions to food-related traditions. Mollo District, in East Nusa Tenggara, Indonesia, presents a compelling case where women play a vital role in promoting local gastronomy. This study aims to analyse the role of women within the ecofeminist framework in promoting local food to support gastronomic tourism in Mollo District. The research adopts a qualitative approach using a case study method. Data is collected through observations, interviews, and document analysis, focusing on women's involvement in local food production and promotion. Key findings are, firstly,  women play a crucial role in developing gastronomic tourism through their expertise in domestic tasks, particularly cooking and household management. Secondly, their traditional knowledge and culinary skills align with ecofeminist perspectives, reinforcing their significance in local food sustainability. Lastly, the successful development of Mollo’s gastronomic tourism depends on strengthening human resources, particularly among women, to enhance their contribution to the sector. The implications are recognizing and supporting women's roles in local food promotion can enhance sustainable gastronomic tourism in Mollo District. Furthermore, capacity-building initiatives and policy support are essential to empower women as key agents in tourism development.